Role of BRCA Mutation and HE4 in Predicting Chemotherapy Response in Ovarian Cancer: A Retrospective Pilot Study - Francesco Plotti; Corrado Terranova; Federica Guzzo; Carlo De Cicco Nardone; Daniela Luvero; Martina Bartolone; Camilla Dionisi; Domenico Benvenuto; Silvia Fabris; Massimo Ciccozzi; Violante Di Donato; Pierluigi Benedetti Panici; et al. (Biomedicines, 2021)
Even though 80% of patients with High-Grade Serous Ovarian Cancer respond to standard first-line chemotherapy, a majority of them could relapse in the following five years due to a resistance to platinum. Human Epididymis protein 4 (HE4) is one of the most promising markers in predicting platinum therapy response. This pilot study aims to evaluate the potential role of HE4 value in predicting chemotherapy response in BRCA mutated patients and in BRCA wild-type (non-mutated) ones. We selected 69 patients, affected by High-Grade Serous Ovarian Cancer, and optimally debulked and submitted to standard chemotherapy protocols. HE4 was dosed during every chemotherapy course. Patients were classified as platinum-resistant and platinum-sensitive. According to BRCA mutation test, patients were further divided into BRCA wild-type (53 patients), and BRCA mutated (16 patients). 35 patients out of 69 (52%) were platinum-sensitive (recurrence > 12 months), while 33 patients (48%) were platinum-resistant (recurrence < 12 months). Thus, in the total population, HE4 performed as a marker of chemosensitivity with a sensibility of 79% and a specificity of 97%. In the BRCA WT group, 23 patients out of 53 (43%) were platinum-sensitive, while 30 patients out of 53 (57%) were platinum-resistant. In the BRCA WT group, HE4 performed as a predictive marker of chemosensitivity with a sensibility of 80% and a specificity of 100%. In the BRCA mutated group, 13 patients out of 16 (82%) were platinum-sensitive, while 3 patients (18%) were platinum-resistant. In the BRCA mutated group, HE4 performed as a predictive marker of chemosensitivity in all patients. The ability to detect platinum-resistant patients before tumor relapse probably could open new therapeutic scenarios.